A review on optimization in polymer processing - Gaspar-Cunha, A. (2022)
The use of optimization computational tools is of primordial importance for the polymer processing industry, as they provide the means for improving the efficiency of the process without requiring time-consuming and expensive procedures. This review aims to evaluate the application of optimization methodologies to the most important polymer processing technics, including, single and twin-screw extrusion, dies and calibrators, blow-moulding, injection moulding and thermoforming. The most important features of an optimization system will be identified to identify the best practices for each particular situation. These features include the nature of the objective function (single or multi-objective), the type of optimization algorithm, the modelling routine used to evaluate the solutions and the parameters to be optimized. First, the state-of-the-art optimization methodologies generally employed is presented. This will be followed by a detailed review of the literature dealing with this subject. This will be completed by a discussion taking into account the features referred to above. Therefore, it was possible to show that different optimization techniques can be applied to polymer processing with great success.